In silico design of a capsid vertex component 1 protein targeted multi-epitope vaccine against cytomegalovirus - Nabin, Md. Naimur Rahman (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2024.